2020
DOI: 10.3390/ijerph17217752
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior among Young Adolescents in 68 LMICs, and Their Relationships with National Economic Development

Abstract: It is unclear whether physical activity and sedentary behavior are associated with economic development in low- and middle-income countries (LMICs). We aimed to assess the association between these two behaviors and country economic development among young adolescents in LMICs. Data came from the Global School-based Student Health Survey (GSHS) conducted between 2009 and 2016 in 68 LMICs. A total of 180,298 adolescents aged 12–15 years were included; 15.3% of young adolescents achieved the recommended level fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
3
13
0
2
Order By: Relevance
“…Previous studies have shown that PA levels of children and adolescents are signi cantly correlated with the economic development where they live (25). Here, we showed that areas of higher economic development were associated with lower levels of MVPA among children and adolescents, a nding consistent with previous global studies(6, 26).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that PA levels of children and adolescents are signi cantly correlated with the economic development where they live (25). Here, we showed that areas of higher economic development were associated with lower levels of MVPA among children and adolescents, a nding consistent with previous global studies(6, 26).…”
Section: Discussionsupporting
confidence: 92%
“…This epidemiologic transition has been identified in related fields of research, such as obesity, where it has been shown that in countries in transition, groups with higher incomes are the first to shift to a more sedentary lifestyle before those of lower income ( 28 ). Research among adolescents in 68 LMIC has also reported that increases in a country’s economic development were coupled with higher levels of sedentary behavior among both sexes ( 29 ). Our findings provide preliminary evidence of a potential sedentary behavior transition that appears to begin in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Macroeconomic indicators are associated with different domains of physical activity, especially for leisure physical activity in women 39 . According to Ma et al, comparing the lowest to the highest quintiles of a country's purchasing power parity per capita, both physical activity and sedentary behaviour increased 40 . Physical activity could influence nutritional status, and thus create uncertainty in the moderation effect of economic status in the association between early life famine exposure and MAFLD in men and in women.…”
Section: Discussionmentioning
confidence: 99%